2020
DOI: 10.1002/pen.25524
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation on flexural behavior of acrylonitrile‐butadiene‐styrene polymer

Abstract: Acrylonitrile‐butadiene‐styrene (ABS) is an extensively utilized rubber‐toughened amorphous thermoplastic in industry. Compared to other amorphous thermoplastics, the most promising mechanical quantity of ABS is its high impact resistance. Thus, understanding the mechanical response of ABS to multiaxial loads is of the great industrial concern. The primary objective of this study was to characterize the flexural response of ABS by conducting three‐point bending tests at two distinct deformation rates of 5 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…13 Apart from the strain rate and temperature influences, hydrostatic pressure also plays an important role in the yield behavior of ABS. 8,14,15 The hydrostatic pressure effect on the yield behavior of ABS can be comprehended from its dissimilar material behavior observed between tension and compression. 14,16 ABS behaves considerably stiffer under compression compared to tension.…”
Section: Introductionmentioning
confidence: 99%
“…13 Apart from the strain rate and temperature influences, hydrostatic pressure also plays an important role in the yield behavior of ABS. 8,14,15 The hydrostatic pressure effect on the yield behavior of ABS can be comprehended from its dissimilar material behavior observed between tension and compression. 14,16 ABS behaves considerably stiffer under compression compared to tension.…”
Section: Introductionmentioning
confidence: 99%
“…Styrene enhances the rigidity and ease of formation of polymer. [ 40 ] ABS is widely used in various applications, namely, automotive instrument panel, car bumper, door handles, seat belt fastening, and radiator grills. [ 52 ] Table 3 shows material properties of ABS used for the present investigation.…”
Section: Methodsmentioning
confidence: 99%
“…From literature survey, it is observed that several attempts have been made to investigate the influence of process parameters on mechanical properties of ME fabricated parts of standard sizes recommended by International Organization for Standardization (ISO) and American Society for Testing and Materials (ASTM) such as ISO 178, ASTM D638, ASTM D695, and ASTM D790. [35][36][37][38][39][40] Some researchers have studied the effect of geometric parameters on mechanical properties of tetra-anti-chiral auxetic structures of various polymeric materials. [10,17,19,41,42] However, very limited research work has been reported on studying the influence of process parameters of material extrusion on mechanical properties of tetra-anti-chiral structures.…”
Section: Introductionmentioning
confidence: 99%
“…Also, modified ethylene-propylene-diene terpolymer prepared by solution polymerization was introduced to toughen SAN resin [7,8], a mass of solvent was used here, and the product conversion rate was low [9]. It was generally accepted that adding acrylonitrilebutadiene-styrene copolymer (ABS) was a successful and efficient way to toughen SAN resin [10,11]. Nevertheless, the double bonds (C=C) in polybutadiene (PB) rubbery core of ABS particles are prone to deterioration and cross-linking due to oxygen, ultraviolet (UV), and other severe environmental circumstances, which results in poor aging resistance, weatherability, and antidiscoloration [12,13].…”
Section: Introductionmentioning
confidence: 99%